Chronic Effect Various Type of Exercises to Fasting Blood Glucose and Insulin Resistance - Machrina, Yetty; Purba, Ambrocious; Lindarto, Dharma; Daulay, Milahayati (Sumatera Medical Journal, 2019)
Exercise is non-pharmacological management for Diabetes Mellitus (DM) type-2. Previous study found that both eerobic and interval training improved insulin resistance. The aim of this study was to analyze the chronic effect various type of exercises to fasting blood glucose (FBG) and insulin resistance in DM type-2 model rats. It was an experimental study, twenty male Wistar rats, age 8 weeks, weight 150-180 gram as the object. Rats were given high fed diet for 4 weeks then injected streptozocin dose 30 mg/kgBB in citrate buffer pH 4.5 i.p, and 45 mg/kgBB at the following week. Groups were divided into i.e moderate continous training (MCT), severe continous training (SCT), slow interval training (SIT), and fast interval training (FIT). All groups were treated with ran on the treadmill three times a week for 8 weeks. Fasting blood glucose and fasting insulin were checked before and after intervention. Insulin resistance was determined by calculating HOMA-IR. Data analized with paired t-test (p<0,05). The results shown that all group significantly decreased fasting blood glucose and insulin resistance (p <0,05) after eight weeks exercise except insulin resistance in MCT group. Fasting blood glucose and insulin resistence post-test was found lowest in SIT groups in this study. In conclucions chronic effect of aerobic continous and aerobic interval in various intensity can decrease fasting blood glucose and insulin resistance in DM type-2 rat model. Slow interval training was the best exercise model to decrease insulin resistance.